A low temperature flat plate solar collector - Hawlader, Mohammad Nurul Alam; Ullah, MD. Zakir; Than Htut, Maung (IIUM Press, 2011)
The performance of a low temperature solar collector, which acts as an evaporator of a heat pump system, has been investigated. An experimcntal setup has been designed, fabricated and tested under the meteorological conditions of Singapore. Refrigerant 134a has been used in the experiments. Effects of various parameters have been considered. Results show that, with the increase in collector tube length, the dryness fraction of the fluid increases leading to an increase in the heat transfer coefficient between the tube wall and fluid. Results also show that collector is very sensitive to solar radiation. If solar radiation increases, the mass flow rate of fluid inside the collector increases, which increases the collector efficiency as more heat is absorbed. Collector efficiency increases with irradiation, reaches a maximum and then decreases. Collector efficiency, as high as about 0.85 was obtained, which could be attributed to the low temperature operation of the collector.